Rv3033, as an Emerging Anti-apoptosis Factor, Facilitates Mycobacteria Survival via Inhibiting Macrophage Intrinsic Apoptosis - Zhang, Wei; Lu, Qian; Dong, Yuanshu; Yue, Yan; Xiong, Sidong (Frontiers in Immunology, 2018)
Apoptosis inhibition is a critical strategy of mycobacteria facilitating its survival in macrophages, but the underlying mechanism is not completely understood. In this study, we found that Rv3033, a secreted virulence factor of mycobacteria, played an important role in bacillary survival within macrophages. Forced over-expressed of Rv3033 in macrophages could efficiently resist mycobacteria-induced early and late apoptosis, accompanied with the obvious increased cellular bacterial burden. By exploring the underlying mechanism, we found that Rv3033 efficiently repressed the intrinsic (caspase-9 meditated), but not the extrinsic (caspase-8 mediated) apoptotic pathway in mycobacteria-infected macrophages. And this repression relied on the orchestrating blockade of both mitochondrial cytochrome c release and endoplasmic reticulum (ER) stress PERK branch activation. Our study uncovered a novel function of mycobacterial virulence factor Rv3033 as an anti-apoptotic protein, which may provide a new target for tuberculosis (TB) treatment.